The nexus of time poverty and well-being of women from poor households: a Malaysian Indian case scenario - Nithiya, Guna Saigaran; Premalatha Karupiah (Penerbit Universiti Kebangsaan Malaysia, 2020)
Time autonomy is a core component in measuring the well-being of humans. The interrelation of time and well-being explains the autonomy one holds towards their time and improves their well-being. Scholars have noted that gendered aspects of well-being are always reflected through time poverty. Time autonomy is not always equal for men and women due to the interference of gender complexities in a household. In traditional societies, men’s time is often dedicated to their role as breadwinners while women’s time is often allocated for multiple roles (i.e. caregiver, mother and wife) in the household. Studies have shown that women’s time allocation is always dedicated to their unpaid roles, which add value for the household members but often reduces their own personal well-being. Poor women have been identified as a group greatly affected by time poverty, which pushes them away from attaining well-being. This study intends to show the spectrum of time poverty experiences of Malaysian Indian women which constraints them from attaining physical and mental well-being. Data was gathered through in-depth interviews with twelve Indian women from B40 households in Sungai Petani and Kulim, Kedah, Malaysia. The findings of this study revealed that excessive weight of household chores, performing multiple roles simultaneously and minimal investment towards personal development as the three important themes. Using the themes and narration of poor Indian women, time poverty and its effects on well-being were explored in this study.